Environment Management Systems in Indian Small and Medium-Sized Enterprises - Singh, Mitrabinda; Brueckner, Martin; Padhy, P. (Academy of Taiwan Business Management Review, 2012)
This paper investigates the challenges small and medium-sized enterprises (SMEs) face in India with regards to their generally poor environmental management track record. In this context, the paper explores the status and effectiveness of Environmental Management Systems (EMSs) as a means of improving the environmental management performance of Indian SMEs as well as the applicability of the formal uptake of ISO 14001 (uncertified or certified). Indian SMEs are responsible for producing large amounts of waste affecting environmental quality but also firms’ international reputation in environmentally sensitive markets. While national policies support the greening of medium size enterprises (MSEs) by way of reimbursing firms 75 per cent of the cost of ISO 14001 certification, businesses are not supported with the cost for “continuous improvement”, which is a major barrier for Indian SMEs when implementing and building up an EMS. This paper is informed by a detailed review of international research on the SME experience with EMSs, examining whether EMS uptake can help SMEs not only improve their environmental performance but also assist in terms of becoming internationally competitive and gaining access to global export markets. This paper points to a need of a country-specific and sector-specific investigation of the relationship between small firms’ EMS uptake and their environmental management performance, based on an analysis of the international EMS experience and the status of EMS in Indian SMEs. Such a research agenda also ought to address the question of relevance and applicability of formal standards such as the ISO 14001 to the Indian context.